Lipid Modulation of Intravascular and Cellular Sodium Handling:Mechanistic Insights and Potential Clinical Implications - K.B. Amaral, Andre C.; Sposito, Andrei C. (Current Vascular Pharmacology, 2006)
Lipid metabolism can modulate structural and functional characteristics of the vascular system. Recent studies suggested that dyslipidemia may also affect the hemodynamic response to salt intake through the impairment of intravascular volume regulation and cellular sodium handling. Indeed, dyslipidemia may affect sodium homeostasis through several pathways, including defective nitric oxide and eicosanoid production, enhanced renin-angiotensin system activity and increased sympathetic response. Moreover, dyslipidemia directly affects cellular membrane viscosity and modifies membrane ion transport activity. In line with this evidence, attenuation of the above mentioned mechanisms has been demonstrated after lipid-lowering treatment. From the clinical point of view, such interaction between plasma lipids and sodium homeostasis may adversely affect the clinical presentation of diseases such as salt-sensitive hypertension, congestive heart failure, renal diseases with proteinuria or sodium retention. This review considers the interplay between plasma lipids and sodium homeostasis and its potential clinical implication.
Keywords: hypertension